Technical Assistance Evaluation Program : Findings of Evaluations and Updated Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Kyrgyz Republic -- Joint Economic Assessment: Reconciliation, Recovery and Reconstruction; Prepared by the Asian Development Bank, International Monetary Fund, and The World Bank; With the participation of Eurasian Development Bank, European Bank for Reconstruction and Development, European Commission, International Finance Corporation, and The United Nations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country TA Priority; IMF TA; PP; TA Department; TA Intervention; China, People's Republic of